MCAT critical analysis and reasoning skills review - Macnow, Alexander Stone (Kaplan Publishing, 2016)
"The most effcient learning for the MCAT results you want. Kaplan's MCAT Critical Analysis and Resoning Skills (CARS) Review has all the information and strategies you need to score higher on the MCAT. This book features more practice than any other guide, plus targeted startegy review, opportunities for self-analysis, a complete online center, and thorough instruction on all of the critical thinking skills necessary for MCAT success--from the creators of the #1 MCAT prep course."--page [4] of cover.